Democracy In Indonesia's Cross-Standards - lusia indrastuti (LEGAL BRIEF, 2022)
Indonesia as a country with a democratic system. The government is administered by the people, for the people, and by the people. Indonesia has gone through multiple periods of democracy, and is currently in a period of transformation. The plurality of Indonesian society has a significant impact on the creation of political parties and favors the formation of a multi-party system in Indonesia. The presence of political parties as foundations of democracy or the execution of popular sovereignty are, of course, justified in a democratic state. General elections are used to carry out democracy when political parties are involved and positions of authority need to be filled.